Visceral leishmaniasis: Recent updates - Jaya Chakravarty; Amartya Seth; Shyam Sundar (Annals of Medical Science and Research)
Visceral leishmaniasis (VL), a severe neglected tropical disease, presents a substantial global health burden, with an estimated 1 million new cases annually. Although cutaneous leishmaniasis (CL) is more prevalent, VL is the deadliest form, particularly in regions such as the Indian subcontinent, East Africa, and Brazil. The disease is caused by Leishmania donovani and transmitted through infected sandflies. Advances in VL management have significantly reduced the number of cases, particularly in India, Nepal, and Bangladesh. However, challenges persist due to human immunodeficiency virus-VL (HIV-VL) coinfection, which exacerbates disease severity and treatment resistance. Effective diagnostic techniques such as polymerase chain reaction and rk39 antigen tests are essential for timely identification of VL, though limitations persist in HIV-positive patients and asymptomatic carriers. Current treatment options, including liposomal amphotericin B and miltefosine, have shown high efficacy, with combination therapies offering promising results in addressing drug resistance and reducing the treatment duration. Post kala-azar dermal leishmaniasis (PKDL) poses a significant challenge to VL elimination, as it serves as a reservoir for ongoing transmission. Shorter, safer regimens are needed, particularly for endemic regions such as East Africa, where traditional treatments are less effective. Continued global collaboration is critical to achieve sustained progress in the elimination of VL and its complications, particularly for vulnerable populations affected by coinfections and drug resistance.